Preparation method of sulfide solid electrolyte film
By preparing sulfide solid electrolyte thin film, the leakage and flammable problem of liquid electrolytes in lithium ion batteries are solved, the battery ionic conductivity and cycle performance are improved, and the generation of lithium branches is reduced.
Patent Information
- Application Number
- CN202411575590.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-01-24
AI Technical Summary
The organic liquid electrolytes used in existing lithium-ion batteries have risks of leakage and flammability, and the rechargeable lithium-ion batteries repeatedly peel off and plating in the organic liquid electrolyte will produce lithium dendrites, resulting in internal short circuits.
The preparation method of a sulfide solid -state electrolyte film is used. After pre -treatment of the polymer base, dissolved and stirred, add lithium hyperchloride and sulfide powder to make a film through the flow method and make the sulfide solid state through thermal solid. Electrolytic film.
It improves the ionic conductivity of solid-state batteries, has high rate and long cycle performance, solves the leakage and flammability problems of liquid electrolyte, and reduces the generation of lithium dendrites.
Smart Images

Figure CN119361842A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electrolyte film preparation, and in particular to a method for preparing a sulfide solid electrolyte film. Background Art
[0002] Currently, lithium-ion batteries (LIBs) are important components of various devices, such as electric vehicles, smart devices, flexible devices, and energy storage systems. The organic liquid electrolytes currently used in commercial LIBs are problematic due to the risk of leakage and flammability, which could lead to huge disasters, and the repeated stripping and plating of rechargeable lithium-ion batteries in organic liquid electrolytes can produce lithium dendrites, which can penetrate the separator and cause internal short circuits. Summary of the invention
[0003] The purpose of the present invention is to provide a method for preparing a sulfide solid electrolyte film. The prepared sulfide solid electrolyte film is beneficial to improving the ionic conductivity of a solid-state battery and has high rate and long cycle performance.
[0004] To achieve the above object, the present invention provides a method for preparing a sulfide solid electrolyte film, comprising the following steps: Step 1: pre-treating the polymer substrate, dissolving the polymer substrate in a solvent and stirring until the solution becomes a transparent viscous liquid; Step 2: adding lithium perchlorate to the transparent mucus obtained in step 1 and stirring to obtain a uniform slurry, and adding sulfide powder to the slurry and stirring to obtain a stirred mucus; Step 3: The stirred mucus obtained in step 2 is made into a film by a casting method, and then made into a sulfide solid electrolyte film by thermal curing.
[0005] Preferably, the specific operation of the pretreatment in step 1 is: placing the polymer substrate in a drying oven and drying it for 12-36 hours.
[0006] Preferably, the polymer substrate in step 1 includes one or more of polyethylene oxide, polyacrylonitrile, polymethyl methacrylate, polyvinylidene fluoride and polyvinylidene fluoride-hexafluoropropylene, and the solvent includes one or both of DMF and NMP.
[0007] Preferably, the stirring temperature in step 1 is 60-70° C., and the stirring time is 15-30 min.
[0008] Preferably, in step 1, the amount of the polymer substrate used is 1-2 g, and the amount of the solvent used is 9-11 g.
[0009] Preferably, the sulfide in step 2 includes one or both of binary sulfide and ternary sulfide, wherein the binary sulfide includes Li3PS4 and Li7P3S11 , ternary sulfides include Li 10 GeP2S 12 and Li6PS5X.
[0010] Preferably, the lithium salt in step 2 includes one or more of lithium perchlorate, lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium bis(difluorosulfonylimide), and lithium bis(trifluoromethylsulfonylimide), wherein the amount of the lithium salt is 0.1-0.6 g, and the stirring time after adding the lithium salt is 2-3 h.
[0011] Preferably, in step 2, the mass of the sulfide powder is 1-5% of the mass of the polymer substrate, and the stirring time after adding the sulfide is 7-8 hours.
[0012] Preferably, the temperature of thermal curing in step three is 50-100°C.
[0013] Preferably, step 1, step 2 and step 3 are carried out in a dry room, i.e., under environmental conditions with a dew point of -30°C.
[0014] Therefore, the present invention adopts the above-mentioned method for preparing a sulfide solid electrolyte film, which has the following beneficial effects: (1) The solid-state battery assembled from sulfide solid electrolyte film exhibits good electrochemical performance.
[0015] (2) This preparation method provides a feasible strategy and method for the development of solid-state electrolytes and solid-state batteries with high ionic conductivity and high mechanical properties, laying a good foundation for the research of solid-state electrolytes and the development of solid-state batteries.
[0016] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 is a SEM image of a sulfide solid electrolyte film in an embodiment of a method for preparing a sulfide solid electrolyte film of the present invention; Figure 2 is an LSV curve diagram of a sulfide solid electrolyte film in an embodiment of a method for preparing a sulfide solid electrolyte film of the present invention; Figure 3 It is an EIS curve diagram of a sulfide solid electrolyte film in an embodiment of a method for preparing a sulfide solid electrolyte film of the present invention. DETAILED DESCRIPTION
[0018] The technical solution of the present invention is further described below through the accompanying drawings and embodiments.
[0019] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by one having ordinary skills in the field to which the present invention belongs.
[0020] The present invention provides a method for preparing a sulfide solid electrolyte film. The following steps are all required to be carried out in a dry room, i.e., under an environmental condition where the dew point is -30°C, and include the following steps: Step 1: Place the polymer substrate in a drying oven and dry it for 12-36 hours to pre-treat the polymer substrate. After the pre-treatment, dissolve 1-2g of the polymer substrate in 9-11g of solvent and stir at 60-70°C for 15-30min until the solution becomes a transparent viscous liquid.
[0021] The polymer substrate includes one or more of polyoxyethylene (PEO), polyacrylonitrile (PAN), polymethyl methacrylate (PMMA), polyvinylidene fluoride (PVDF) and polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), and the solvent includes one or both of DMF and NMP.
[0022] PVDF is a semi-crystalline polymer obtained by polymerization of 1,1-difluoroethylene monomer. The polymer has a strong electron-withdrawing group - CF2 and a high dielectric constant, which is conducive to the dissociation of lithium salts. At the same time, it has the characteristics of good mechanical properties, high thermal stability and excellent film-forming properties. Due to the symmetric structure and regular arrangement of PVDF and high crystallinity, its ionic conductivity at room temperature is low. The PVDF-HFP obtained after the introduction of hexafluoropropylene (-HFP) groups increases the amorphous phase region of the polymer and has the advantages of high room temperature ionic conductivity, low glass transition temperature and excellent heat resistance. In addition, Li et al. found that PVDF-HFP polymer can significantly improve the hydrolysis resistance of sulfide electrolytes. This is because PVDF-HFP attached to the surface of sulfide particles can serve as a protective isolation layer between the electrolyte and H2O, thereby avoiding the hydrolysis reaction caused by contact, thereby reducing the self-instability caused by sulfide moisture absorption.
[0023] Step 2: Add 0.1-0.6 g of lithium salt to the transparent mucus obtained in step 1 and stir for 2-3 hours to obtain a uniform slurry. Add sulfide powder to the slurry and stir for 7-8 hours to obtain a stirred mucus. The mass of the sulfide powder is 1-5% of the mass of the polymer substrate.
[0024] Sulfides include one or two of binary sulfides and ternary sulfides, wherein the binary sulfides are composed of Li2S and P2S5, including Li3PS4 and Li7P3S 11 The ternary sulfide is composed of Li2S, P2S5 and MS2 (M = Si, Ge, Sn), including Li 10 GeP2S 12(LGePS) and Li6PS5X, etc. Among them, Li 10 GeP2S 12 The electrolyte has become one of the most promising inorganic solid electrolytes due to its high room temperature lithium ion conductivity, relatively low cost and high stability.
[0025] The lithium salt includes one or more of lithium perchlorate, lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium bis(difluorosulfonylimide), and lithium bis(trifluoromethylsulfonylimide).
[0026] Step 3: The stirred mucus obtained in step 2 is made into a film by a casting method, and then heat-cured at 50-100° C. to form a sulfide solid electrolyte film.
[0027] Embodiment 1 Step 1: Place PVDF-HFP in a drying oven and dry it for 24 hours to pre-treat PVDF-HFP. After the pre-treatment, dissolve 1 g of PVDF-HFP in 9 g of DMF and stir at 60° C. for 15 minutes until the solution becomes a transparent viscous liquid.
[0028] Step 2: Add 0.1 g of lithium perchlorate to the transparent mucus obtained in step 1 and stir for 2 h to obtain a uniform slurry. Add LGePS powder (1% of the mass of the polymer substrate) to the slurry and stir for 7 h to obtain a stirred mucus.
[0029] Step 3: The stirred mucus obtained in step 2 is made into a film by a casting method, and then heat-cured at 70° C. to form a sulfide solid electrolyte film.
[0030] Embodiment 2 Step 1: Place PVDF-HFP in a drying oven and dry it for 24 hours to pre-treat PVDF-HFP. After the pre-treatment, dissolve 1 g of PVDF-HFP in 10 g of NMP and stir at 60° C. for 15 minutes until the solution becomes a transparent viscous liquid.
[0031] Step 2: Add 0.2 g of lithium perchlorate to the transparent mucus obtained in step 1 and stir for 2 h to obtain a uniform slurry. Add LGePS powder (2% of the mass of the polymer substrate) to the slurry and stir for 7 h to obtain a stirred mucus.
[0032] Step 3: The stirred mucus obtained in step 2 is made into a film by a casting method, and then heat-cured at 70° C. to form a sulfide solid electrolyte film.
[0033] Embodiment 3 Step 1: Place PVDF-HFP in a drying oven and dry it for 24 hours to pre-treat PVDF-HFP. After the pre-treatment, dissolve 1 g of PVDF-HFP in 9 g of DMF and stir at 60° C. for 15 minutes until the solution becomes a transparent viscous liquid.
[0034] Step 2: Add 0.3 g of lithium perchlorate to the transparent mucus obtained in step 1 and stir for 2 h to obtain a uniform slurry. Add LGePS powder (3% of the mass of the polymer substrate) to the slurry and stir for 7 h to obtain a stirred mucus.
[0035] Step 3: The stirred mucus obtained in step 2 is made into a film by a casting method, and then heat-cured at 70° C. to form a sulfide solid electrolyte film.
[0036] Embodiment 4 Step 1: Place PVDF-HFP in a drying oven and dry for 24 hours to pre-treat PVDF-HFP. After the pre-treatment, dissolve 2 g of PVDF-HFP in 9 g of DMF and stir at 70° C. for 15 minutes until the solution becomes a transparent viscous liquid. Step 2: Add 0.4 g of lithium perchlorate to the transparent mucus obtained in step 1 and stir for 2 h to obtain a uniform slurry, add LGePS powder (4% of the mass of the polymer substrate) to the slurry and stir for 7 h to obtain a stirred mucus; Step 3: The stirred mucus obtained in step 2 is made into a film by a casting method, and then heat-cured at 70° C. to form a sulfide solid electrolyte film.
[0037] Embodiment 5 Step 1: Place PVDF-HFP in a drying oven and dry for 24 hours to pre-treat PVDF-HFP. After the pre-treatment, dissolve 2 g of PVDF-HFP in 9 g of DMF and stir at 70° C. for 15 minutes until the solution becomes a transparent viscous liquid. Step 2: Add 0.5 g of lithium perchlorate to the transparent mucus obtained in step 1 and stir for 2 h to obtain a uniform slurry, add LGePS powder (5% of the mass of the polymer substrate) to the slurry and stir for 7 h to obtain a stirred mucus; Step 3: The stirred mucus obtained in step 2 is made into a film by a casting method, and then heat-cured at 70° C. to form a sulfide solid electrolyte film.
[0038] Comparative Example 1 Step 1: Place PVDF-HFP in a drying oven and dry for 24 hours to pre-treat PVDF-HFP. After the pre-treatment, dissolve 1 g of PVDF-HFP in 9 g of DMF and stir at 60° C. for 15 minutes until the solution becomes a transparent viscous liquid. Step 2: Add 0.1 g of lithium perchlorate to the transparent mucus obtained in step 1 and stir for 2 h to obtain a uniform slurry.
[0039] Step 3: The slurry obtained in step 2 is made into a film by a casting method, and then heat-cured at 70° C. to form a sulfide solid electrolyte film.
[0040] In order to verify the feasibility of the solid electrolyte membrane prepared by the method of the present invention, the morphology of the solid electrolyte membrane was observed by scanning electron microscopy (SEM); the Lsv curve of the button cell (lithium sheet / polymer membrane / steel sheet) was tested by linear voltammetry; and the phase structure of the solid electrolyte membrane was detected by DX-2700 X-ray diffractometer (XRD).
[0041] Depend on Figure 1 It can be seen that the prepared sulfide solid electrolyte film has a uniform pore structure. The sulfide solid electrolyte film has the advantages of high density, uniform particle distribution, good interface contact, nanoscale structure and stable structure. These characteristics make it have potential application value in solid-state batteries.
[0042] Figure 2 This is the LSV curve of the prepared sulfide solid electrolyte film. It can be seen from the figure that as the voltage increases, the current gradually increases. When the voltage is low, the current does not change much, but after the voltage reaches a certain value, the current increases rapidly. This shows that the sulfide solid electrolyte film has a lower conductivity at low voltage, while the conductivity increases significantly at high voltage, and the polarization voltage of the solid-state battery curve with sulfide added is higher than the polarization voltage of the solid-state battery without sulfide added.
[0043] Figure 3 This is the EIS curve of the sulfide solid electrolyte film. It can be seen from the figure that after the addition of sulfide, its resistance value decreases, and then the ionic conductivity increases; the impedance value of the impedance spectrum of 1% LGePS in the high frequency band is significantly lower than that of 0% LGePS, which indicates that the sulfide solid electrolyte film with 1% LGePS added has lower impedance, thereby improving the conductivity of the electrolyte. Lower impedance means that the electrolyte can transport ions more effectively in the battery, thereby improving the performance and efficiency of the battery.
[0044] Therefore, the present invention adopts the above-mentioned method for preparing a sulfide solid electrolyte film, which provides a feasible strategy and method for the development of solid electrolytes and solid-state batteries with high ionic conductivity and high mechanical properties, and lays a good foundation for the research of solid electrolytes and the development of solid-state batteries.
[0045] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. A method for preparing a sulfide solid electrolyte film, characterized in that: The following steps are involved: Step 1: pre-treating the polymer substrate, dissolving the polymer substrate in a solvent and stirring until the solution becomes a transparent viscous liquid; Step 2: adding lithium perchlorate to the transparent mucus obtained in step 1 and stirring to obtain a uniform slurry, and adding sulfide powder to the slurry and stirring to obtain a stirred mucus; Step 3: The stirred mucus obtained in step 2 is made into a film by a casting method, and then made into a sulfide solid electrolyte film by thermal curing.
2. The method for preparing a sulfide solid electrolyte film according to claim 1, characterized in that: The specific operation of the pretreatment in step 1 is: placing the polymer substrate in a drying oven and drying it for 12-36 hours.
3. The method for preparing a sulfide solid electrolyte film according to claim 1, characterized in that: The polymer substrate in step 1 includes one or more of polyoxyethylene, polyacrylonitrile, polymethyl methacrylate, polyvinylidene fluoride and polyvinylidene fluoride-hexafluoropropylene, and the solvent includes one or both of DMF and NMP.
4. The method for preparing a sulfide solid electrolyte film according to claim 1, characterized in that: The stirring temperature in step 1 is 60-70° C. and the stirring time is 15-30 min.
5. The method for preparing a sulfide solid electrolyte film according to claim 1, characterized in that: In step 1, the amount of the polymer substrate used is 1-2 g, and the amount of the solvent used is 9-11 g.
6. The method for preparing a sulfide solid electrolyte film according to claim 1, characterized in that: The sulfide in step 2 includes one or two of binary sulfide and ternary sulfide, wherein the binary sulfide includes Li3PS4 and Li7P3S 11 , ternary sulfides include Li 10 GeP2S 12 and Li6PS5X.
7. The method for preparing a sulfide solid electrolyte film according to claim 1, characterized in that: In step 2, the lithium salt includes one or more of lithium perchlorate, lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium bis(difluorosulfonylimide), and lithium bis(trifluoromethylsulfonylimide), wherein the amount of the lithium salt is 0.1-0.6 g, and the stirring time after adding the lithium salt is 2-3 h.
8. The method for preparing a sulfide solid electrolyte film according to claim 1, characterized in that: In step 2, the mass of the sulfide powder is 1-5% of the mass of the polymer substrate, and the stirring time after adding the sulfide is 7-8 hours.
9. The method for preparing a sulfide solid electrolyte film according to claim 1, characterized in that: The temperature of thermal curing in step 3 is 50-100°C.
10. The method for preparing a sulfide solid electrolyte film according to claim 1, characterized in that: Step 1, step 2 and step 3 are carried out in a dry room, i.e., under environmental conditions where the dew point is -30°C.
Citation Information
Patent Citations
Lithium ion battery interlayer solid-state electrolyte and a preparation method thereof
CN109802171A
Preparation method of sulfide solid electrolyte film and all-solid-state battery comprising sulfide solid electrolyte film
CN115149089A
Preparation method of sulfide-based ceramic composite electrolyte film
CN116885269A
Electrolyte, composition for electrolyte and lithium battery employing the same
US20190207255A1
Sulfide composite electrolytes for solid-state lithium batteries
US20240055650A1